Dialogue interculturel en ligne: communication «ratée» dans un projet télécollaboratif - Savlovska, Dina; Loizidou, Dora; Ivanova, Viktorija (Kalbotyra, 2021)
Over the past two decades, the development of computer-mediated communication technologies has modified human communication. Increasingly, representatives from diverse linguistic and cultural backgrounds are disposed to a constant negotiation of meanings. The main purpose of this study is to carry out a linguistically grounded analysis of the intercultural dialogue during online asynchronous written exchanges between Latvian and Cypriot students. Based on the politeness theory of Brown and Levinson (1987), which implies that all adult members of society are endowed with two universal aspects: “positive face” and “negative face”, and using the methods of content analysis and discourse analysis, this research analyses the way learners communicate or hide their position concerning sensitive cultural issues. To attain the objective of the present research, a quantitative and qualitative experimental study was conducted. The learners’ public messages in the discussion forums were juxtaposed with their private messages concerning proposed cultural topics. The findings show a strong interdependence between the politeness strategies used by the learners and the intercultural issue discussed. Thus, online intercultural discussions can be qualified as context-dependent and content-dependant. Discussion forum does not seem to be an appropriate environment to facilitate and encourage intercultural discussions about potentially controversial issues.